Artistic movements and cultural policy - Frederico, Celso (Estudos Avançados, 2018)
The revolutionary process in Russia was accompanied by intense artistic ferment. Among the several movements that emerged, the most important were Productivism, Futurism and Proletkult. They all sought blessing of the young Soviet State, which, however, in its first years, did not grant to any of them the monopoly of representation in the arts. This attitude is largely explained by the vision of its main leaders, Lenin and Trotsky. With the rise of Stalinism, a monolithic cultural policy was imposed, which established Socialist Realism as the official aesthetics of the regime.